EFEKTIVITAS PENGGUNAAN ANJUNGAN PENDAFTARAN MANDIRI UNTUK PENDAFTARAN PASIEN RAWAT JALAN PADA RUMAH SAKIT MATA BALI MANDARA DI DENPASAR - I Putu Agus Widiantara; Ni Nengah Karuniati; Muhammad Noor (Jurnal Ilmu Sosial dan Ilmu Politik, 2023)
In the 'new normal' era, people could not gather in queues when registering at the hospital to get outpatient services as usual. To be able to continue serving the people who need these services, Bali Mandara Eye Hospital used registration machine. With regard to the use of this machine, this study was conducted, with qualitative method, to know the effectiveness of the registration machine. The researchers did data presentation, data reduction, and data analysis. The results showed that the registration machine had effectively reduced waiting time at the registration counter even though there were more people using this machine.